Biodiesel from Dodonaea Plant Oil: Synthesis and Characterization—A Promising Nonedible Oil Source for Bioenergy Industry - Bukhari, Syeda Alia Zehra; Ullah, Kifayat; Ahmad, Mushtaq; Zafar, Muhammad; Ullah, Anwar; Sultana, Shazia; Ibrahim, Mohamed Mousa; Hessien, Mahmoud Mohamed; Mersal, Gaber Ahmad Mahmoud; Ghoneim, Sherif Salama Mohamed (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, Dodonaea oil was studied as a potential biodiesel source. Dodonaea (Dodonaea viscosa Jacq.) is an evergreen shrubby plant that thrives in tropical and subtropical conditions. The plant produces high-grade biodiesel in terms of both quantity and quality despite its naturally high fat content. In the transesterification followed by esterification reaction, varied ratios of oil to methanol, constant temperature (60°), reaction duration (1 h), and different catalyst concentrations (0.25–0.75% (w/w) were utilized. A maximum biodiesel yield of 90% was achieved. For fuel characteristic analysis, the prepared biodiesel was specified and compared to ASTM criteria. The chemical composition was verified using analytical techniques such as FT-IR and NMR spectroscopy. As a result of the foregoing, Dodonaea is considered a possible bioenergy source, particularly in the transport sector.